STABILITY INDICATING RP-HPLC ASSAY OF HYDROCODONE AND IBUPROFEN IN TABLETS: HYDROCODONE AND IBUPROFEN ANALYSIS - Kandula, Rama Kumar; Sundararajan, Raja (International Journal of Applied Pharmaceutics, 2019)
Objective: The combination of hydrocodone and ibuprofen is prescribed to temporarily relieve severe pain. A new selective, precise and accurate stability indicating reverse phase high performance liquid chromatography (RP-HPLC) technique was developed for identification and estimation of hydrocodone and ibuprofen in tablets. Methods: The analysis of hydrocodone and ibuprofen was executed on phase Zodiac C18 (250 × 4.6 mm, 5 μm) column with sodium dihydrogen phosphate (0.1M, pH5.0) and methanol (60:40, v: v) as a mobile phase with a flow rate of 1.0 ml/min. The detection and measurement was done at 234 nm. The stability of hydrocodone and ibuprofen was examined under different conditions recommended by ICH, including alkaline, acidic, neutral, oxidative, photolytic and thermal. Results: Hydrocodone and ibuprofen are eluted at 4.019 min and 4.999 min, respectively. The assay method was linear (range: 3.75-11.25 µg/ml and 100-300 μg/ml) with R2values of 0.9996 and 0.9999 for hydrocodone and ibuprofen, respectively. Method was accurate (recovery: 99.65% and 99.37% for hydrocodone and ibuprofen, respectively), precise (RSD: 0.262% and 0.261% for hydrocodone and ibuprofen, respectively), selective and robust. In degradation studies, peaks of degradants did not interfere with the peaks of hydrocodone and ibuprofen. This validated method was applied to assay the content of hydrocodone and ibuprofen in tablets. Conclusion: This method can be opted in the routine quality control test of fixed dose tablet combination comprising of hydrocodone and ibuprofen.